CURRENT RELATIONSHIP BETWEEN ELECTRONIC COMMERCE AND MEXICAN SMES. Theoretical Analysis Under The Vision Based On The Industry - VARGAS-HERNÁNDEZ, José G.; ROSAS, David Iván Pérez (SSD Journal, 2018)
In this essay, first, the current situation in which SMEs in Mexico are related to e-commerce is exposed, since this last one provides a significant opportunity for the improvement of business results for this class of companies. In addition, a review of the empirical literature is provided in which models that allow to measure the degree of adoption of ecommerce by SMEs are exposed, as well as to understand the behavior of these economic agents with the e-commerce worldwide as in territory Mexican. Finally, an analysis is carried out under the model of the Porter pyramid in relation to Mexican SMEs and e-commerce. The objective of this essay is to present a different approach on the Porter’s Five forces model and to make the reader aware of the topic of industrial competence and e-commerce in Mexico.